2016
DOI: 10.1002/chem.201604923
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced Sensitivity and Piezochromic Contrast through Single‐Direction Extension of Molecular Structure

Abstract: Two piezochromic materials containing phenanthro[9,10-d]imidazole and tetraphenylethylene (M1 and M2) were developed. A supra-amplification piezochromic effect originating from their various long-to-short axis ratios was discovered in high-pressure experiments. Based on the linear relationship between applied pressure and emission-peak wavelength during pressurizing and depressurizing cycles, quantitative sensitivity for piezochromism could be denoted. M2 displayed higher piezochromic contrast (102 nm) and bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…[ 10 ] The absorption sidebands of 1CA , 1CB , and 1CC are sequentially shifted and broadened to longer wavelengths, indicating that their energy gaps are gradually reduced. [ 11 ] That is to say, their ICT process are strengthened in turn, so that their emission colors are redshifted.…”
Section: Resultsmentioning
confidence: 99%
“…[ 10 ] The absorption sidebands of 1CA , 1CB , and 1CC are sequentially shifted and broadened to longer wavelengths, indicating that their energy gaps are gradually reduced. [ 11 ] That is to say, their ICT process are strengthened in turn, so that their emission colors are redshifted.…”
Section: Resultsmentioning
confidence: 99%
“…A Raman peak at 998 cm À1 is attributed to the ring breathing, 1130 cm À1 is attributed to the stretching vibration of the C À C single bond formed between ethylene core and adjacent benzene ring in ETTB, 1605 cm À1 is attributed to the C=C stretching vibrations of benzene ring. [18] With increasing pressure, majority of the Raman peaks exhibited obvious blue shifts and gradual reductions in peak intensity (Figure 4), which signified the enhancement in intermolecular interactions. [19] Meanwhile, the absence of peak degeneration and emergence of new peak indicated that no phase or defect transition occurs during the whole pressurization process.…”
Section: Angewandte Chemiementioning
confidence: 98%
“…Imaging and measuring mechanical stresses, such as, compression, friction, and tensile stresses, are some of the challenging goals in recent materials science. [ 1–21 ] Mechano‐responsive materials exhibit visible and/or fluorescent color changes through microscopic structural changes including the chromophore at the molecular scale with the application of macroscopic mechanical stresses. Transfer of macroscopic mechanical stresses to microscopic structures is important for the design of mechano‐responsive color‐changing materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, compression stress was detectable in the range 10 6 –10 10 Pa, namely the order of MPa and GPa, using mechano‐responsive materials in previous works ( Figure e and Figure S1, Supporting Information). [ 7–11,13,15,17,20,21,27–33 ] The facts indicate that the molecular motion leading to color changes is not easily induced by weak compression stress. New strategies are required for the measurement of weak stresses beyond approaches in molecular sciences.…”
Section: Introductionmentioning
confidence: 99%